Manchester triage fuzzy expert system / Azril Asraf Azlan - Azlan, Azril Asraf (2007)
Deaths in hospital often occur within 24 hours of admission. Many of these deaths could be prevented if very sick patients are identified soon after their arrival and treatment is started immediately. This will lead the workload varies from day to day hour to hour which depends on the numbers of attending and its complaint. In addition it also raises the pressure to the medical staffs to make the decision. It is absolutely crucial that there is a system in place to ensure these patients are seen in order of clinical need rather than in order of attendance. Thus to develop system which using Manchester Triage Scale (MTS) technique and fuzzy approach in evaluate the patients is the solutions to this problem. In order to deal with uncertainties that exist in evaluating the patients, the concept of fuzzy is also presented. Additionally a rule-based technique is chosen because the knowledge in this problem domain can be simply transform into rules. In consequence the system initially will help the triage nurses or the practitioners in making decision in evaluating the patients by determine which patients needed the most treatments at that time.